+0

# if r and s are the roots of 2x^2 -5x -7 =0 what is the value of r/s + s/r

0
477
13

if r and s are the roots of 2x^2 -5x -7 =0 what is the value of r/s + s/r?

Guest Jul 5, 2014

#12
+91411
+11

Here is another approach.  I suspect that this is how it was meant to be done.

Given the quadratic equation

$$ax^2+bx+c=0\qquad \mbox{the sum of the roots is } \frac{-b}{a} \mbox{ and the product of the roots is } \frac{c}{a}$$

so

$$2x^2-5x-7=0\qquad r+s= \frac{5}{2}\:\: \mbox{ and }\:\: rs=\frac{-7}{2}$$

Now

$$\dfrac{r}{s}+\dfrac{s}{r}\\\\ =\dfrac{r^2+s^2}{rs}\\\\ =\dfrac{r^2+s^2+2rs-2rs}{rs}\\\\ =\dfrac{(r+s)^2-2rs}{rs}\\\\ =\dfrac{(\frac{5}{2})^2-2\times \frac{-7}{2}}{\frac{-7}{2}}\\\\ =\dfrac{\frac{25}{4}+ \frac{14}{2}}{\frac{-7}{2}}\\\\ =\dfrac{\frac{25}{4}+ \frac{28}{4}}{\frac{-7}{2}}\\\\ =\frac{53}{4}\times\frac{-2}{7}\\\\ =\frac{53}{2}\times\frac{-1}{7}\\\\ =\frac{-53}{14}\\\\ =\:-3\frac{11}{14}$$

Melody  Jul 5, 2014
Sort:

#1
+3450
+5

I'm not quite sure what you mean by "r and s are the roots of..."

Do you mean that r and s are the two values for x in this equation?

This is how I'll solve it. If I misinterpreted the question let me know.

2x2 -5x -7 =0

Let's factor the polynomial and then find the values of x.

(2x+7)(x-1) = 0

------

(2x+7) = 0

2x = -7

x = -3½

------------

(x-1) = 0

x = 1

-------

So let's say r = 3½ and s = 1

Let's put this in the equation.

r/s + s/r

3.5/1 + 1/3.5

12.25/3.5 + 1/3.5

13.25/3.5

Well...that would be the answer.

Sorry if I totally bombed this, I think the problem was that I didn't really understand the question.

NinjaDevo  Jul 5, 2014
#2
+4145
0

YES YOU BOMBED THIS NO POINTS FOR YOU

zegroes  Jul 5, 2014
#3
+11757
+3

Zegroes dont be so selfish in letting people take their points!all points are not for u only!

rosala  Jul 5, 2014
#4
+4145
0

YES ALL MINE MUHAHAHAHA!!!!!!!!!

zegroes  Jul 5, 2014
#5
+3450
0

NinjaDevo  Jul 5, 2014
#6
+11757
+3

NOPE!

but u dont have much left to take home as melody has already taken more than half of them!

rosala  Jul 5, 2014
#7
+4145
0

MELODYS A DINOSAUR OF COURSE SHE NEEDS TO EAT LIKE 10 TONS OF POINTS (meat) A DAY!

zegroes  Jul 5, 2014
#8
+11757
+3

Nothing to say......!

BTW thank god ND ur bomb isnt real or else it would b**w up all the answers!

rosala  Jul 5, 2014
#9
+80785
+5

I think you have the right idea, ND....let's look at the factoring once more...

2x^2 - 5x - 7 = (2x -7) (x + 1)

So the roots are 7/2 and -1

So

(7/2)/(-1) + (-1)/(7/2) =

-7/2 - 2/7   =  -(7/2 + 2/7) = - (49 + 4)/14  = -53/14

I think that might be it ......

CPhill  Jul 5, 2014
#10
+3450
0

Oh i see, my factoring was off.

Thanks CPhill.

NinjaDevo  Jul 5, 2014
#11
+80785
0

I gave you "points" anyway....just a slight mistake....I make 'em all the time!!!  Your approach was correct and that's sometimes more important than just getting the  "right" answer.....

CPhill  Jul 5, 2014
#12
+91411
+11

Here is another approach.  I suspect that this is how it was meant to be done.

Given the quadratic equation

$$ax^2+bx+c=0\qquad \mbox{the sum of the roots is } \frac{-b}{a} \mbox{ and the product of the roots is } \frac{c}{a}$$

so

$$2x^2-5x-7=0\qquad r+s= \frac{5}{2}\:\: \mbox{ and }\:\: rs=\frac{-7}{2}$$

Now

$$\dfrac{r}{s}+\dfrac{s}{r}\\\\ =\dfrac{r^2+s^2}{rs}\\\\ =\dfrac{r^2+s^2+2rs-2rs}{rs}\\\\ =\dfrac{(r+s)^2-2rs}{rs}\\\\ =\dfrac{(\frac{5}{2})^2-2\times \frac{-7}{2}}{\frac{-7}{2}}\\\\ =\dfrac{\frac{25}{4}+ \frac{14}{2}}{\frac{-7}{2}}\\\\ =\dfrac{\frac{25}{4}+ \frac{28}{4}}{\frac{-7}{2}}\\\\ =\frac{53}{4}\times\frac{-2}{7}\\\\ =\frac{53}{2}\times\frac{-1}{7}\\\\ =\frac{-53}{14}\\\\ =\:-3\frac{11}{14}$$

Melody  Jul 5, 2014
#13
+18827
+8

if r and s are the roots of 2x^2 -5x -7 =0 what is the value of r/s + s/r ?

$$ax^2+bx+c=0 \\ \mbox{The roots are: } x_{1,2}= {-b\pm\sqrt{b^2-4ac}\over2a}\\ \mbox{or } x_{1,2}= {-b\pm\sqrt{D}\over2a} \quad \mbox{ set }\quad D=b^2-4ac\\ \mbox{So we have: } r=x_1={-b+\sqrt{D}\over 2a}\\ \mbox{and } s=x_2={-b-\sqrt{D}\over 2a}$$

$$\\ \boxed{{r\over s}+{s\over r} =} {-b+\sqrt{D}\over -b-\sqrt{D}}+{-b-\sqrt{D}\over -b+\sqrt{D}}\\ \\ ={(-b+\sqrt{D})^2 +(-b-\sqrt{D})^2\over (-b-\sqrt{D})(-b+\sqrt{D})}\\\\ ={2(-b)^2+2(\sqrt{D})^2 \over (-b)^2-(\sqrt{D})^2}\\\\ ={2b^2+2D \over b^2-D} \quad | \quad D= b^2-4ac$$

$$\\={2b^2+2b^2-8ac \over b^2-b^2+4ac} \\\\ ={4b^2-8ac \over 4ac} \\\\ ={b^2 \over ac} - 2 \quad | \quad a=2 \quad b=-5 \quad c=-7$$

$$\\={ (-5)^2 \over 2*(-7) } -2 \\\\ ={ 25 \over (-14) } -2 \\\\ ={ -25-2*14 \over 14 } \\\\ ={ -\frac{53} {14} } \\\\ ={ -\frac{14*3+11} {14} } \\\\ ={ -3-\frac{11} {14} } \\\\ \boxed{={ -3\frac{11} {14} }}$$

heureka  Jul 7, 2014

### 18 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details